1990
DOI: 10.1016/0014-5793(90)80240-j
|View full text |Cite
|
Sign up to set email alerts
|

The role of phospholipase A2 in lipid peroxidation‐induced fall of membrane potential of rat liver mitochondria

Abstract: Cumene hydroperoxide (230 PM)-induced fall of the membrane potential takes place only in Ca *+-loaded mitochondria. Inhibitor of phospholipase AZ p-bromphenacyl bromide prevents uncoupling of mitochondria, having no effect on the accumulation of lipid peroxidation products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…The strong evidence supporting phospholipase A 2 involvement in mitochondrial deterioration is that different phospholipase A 2 inhibitors are able to prevent pro-oxidant-induced Ca 2+ efflux from mitochondria. 9,11 However, it was shown later that the hydroperoxide-induced release of Ca 2+ was independent of the accumulation of lipid peroxidation products. 12 It has been also demonstrated that accumulation of phospholipase A 2 reaction products in mitochondria is a consequence, rather than a cause, of the membrane permeability transition.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The strong evidence supporting phospholipase A 2 involvement in mitochondrial deterioration is that different phospholipase A 2 inhibitors are able to prevent pro-oxidant-induced Ca 2+ efflux from mitochondria. 9,11 However, it was shown later that the hydroperoxide-induced release of Ca 2+ was independent of the accumulation of lipid peroxidation products. 12 It has been also demonstrated that accumulation of phospholipase A 2 reaction products in mitochondria is a consequence, rather than a cause, of the membrane permeability transition.…”
Section: Introductionmentioning
confidence: 97%
“…6,7 On the other hand, the changes in membrane permeability in mitochondria exposed to Ca 2+ and oxidants may involve activation of mitochondrial phospholipase A 2 . [8][9][10][11] It was suggested that alteration of the membrane lipid phase (in particular peroxidation of lipids) caused by oxidizing agent stimulates phospholipase A 2 which hydrolyses mitochondrial phospholipids, with a release of free fatty acids and lysophospholipids, both of which may alter mitochondrial membrane barrier properties and dissipate membrane potential. The strong evidence supporting phospholipase A 2 involvement in mitochondrial deterioration is that different phospholipase A 2 inhibitors are able to prevent pro-oxidant-induced Ca 2+ efflux from mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Damage of mitochondrial inner membranes is another attractive hypothesis to explain PT. Permeabilization could be due to alterations of the phospholipid bilayer such as lipoperoxidation (25,26), lysophospholipid accumulation due to increased activity of phospholipase A 2 (27,28), or alterations of the proteins embedded in the membrane (protein oxidation leading to high-molecular weight membrane protein aggregates) (29,30).…”
Section: Introductionmentioning
confidence: 99%